Analisis Tindak Tutur Perlokusi terhadap Kritik Sosial melalui Humor Gelap dalam Video Youtube Somasi: Kajian Pragmatik - Mulyo Kurniati (Multatuli: Jurnal Bahasa dan Sastra Indonesia, 2025)
The popularity of digital media such as YouTube has made it an effective platform for delivering social criticism through entertainment content. One example is the program "Somasi" by Deddy Corbuzier, which combines dark humor with social issues. This research aims to analyze perlocutionary acts in the dark humor of "Somasi" videos on YouTube to understand the hidden meanings and its communicative effects on the audience. The research method used is qualitative descriptive, employing a pragmatic approach through discourse analysis of "Somasi" videos that contain dark humor related to social issues. The results indicate that dark humor in "Somasi" utilizes perlocutionary acts to convey social criticism and sensitive issues in a light yet meaningful manner. The findings reveal four types of perlocutionary acts: (1) expressive perlocutionary acts, (2) representative perlocutionary acts, (3) directive perlocutionary acts, and (4) declarative perlocutionary acts